Microsoft Office for the older and wiser : get up and running with office 2010 and office 2007 - McManus, Sean , 1973- (John Wiley, 2011)
"Are you new to Microsoft Office software? Looking for instructions that aren?t full of complicated computing terms? Microsoft Office for the Older and Wiser can answer all of your queries with its straightforward advice and easy-to-follow layout on using both Office 2010and Office 2007. Completely jargon-free and aimed at those wishing to extend their computing knowledge, Microsoft Office for the Older and Wiser will have you producing documents in Word, spreadsheets in Excel, slideshows in PowerPoint, and emails in Windows Live Mail in no time. Learn how to: Type and format a letter Create an address book Produce personalised invitations Publish a newsletter Form a basic holiday budget Create a photo slideshow Keep a digital recipe book Share and develop ideas over the Internet U3A is a self-help, learning cooperative for those no longer in full-time, gainful employment. Members come together to share their love of learning through educational, creative and leisure activities. U3A offer their members a wide choice of 300+ subjects in areas such as art, foreign languages, music, history, life sciences, literature, poetry, gardening, philosophy, crafts, field studies, archaeology, astronomy and computing. Currently there are over 230,000 members and more than 740 local U3A groups in the UK. Visit U3A online at www.u3a.org.uk"-- Provided by publisher